2017
DOI: 10.1080/10345329.2017.12036076
|View full text |Cite
|
Sign up to set email alerts
|

The Prisoners Review Board of Western Australia: What do the Public Know about Parole?

Abstract: One of the key doctrinal developments of the High Court of Australia in relation to its constitutional limitations jurisprudence is the structured test of proportionality. In recent cases involving the implied freedom of political communication, the Court has indicated that its constitutional adjudicative function will be informed by the extent to which a parliament has, or has not, considered issues of proportionality. In this article, we examine these developments through the parliamentary institutional lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…Similar results have been reported internationally (Ostermann, 2013;Ostermann & Hyatt, 2016). Despite this, the public tend to overestimate the proportion of parolees who reoffend and often express a preference for prisoners to be released unconditionally at the end of their sentence, rather than being paroled (Gately et al, 2017;Roberts, 1988).…”
Section: Parole In the Australian Contextsupporting
confidence: 59%
See 3 more Smart Citations
“…Similar results have been reported internationally (Ostermann, 2013;Ostermann & Hyatt, 2016). Despite this, the public tend to overestimate the proportion of parolees who reoffend and often express a preference for prisoners to be released unconditionally at the end of their sentence, rather than being paroled (Gately et al, 2017;Roberts, 1988).…”
Section: Parole In the Australian Contextsupporting
confidence: 59%
“…There, a larger proportion of respondents agreed (46%) than disagreed (38%) with the idea of parole release (Fitzgerald et al, 2016). A second study, which drew from qualitative interviews with 38 individuals from Western Australia, also revealed mixed support for parole, although also confirming that members of the Australian public hold very little accurate knowledge of this criminal justice process (Gately et al, 2017). These studies did not, however, examine whether Australian men and women differ in their support of parole.…”
Section: List Of Figures and Tablesmentioning
confidence: 95%
See 2 more Smart Citations
“…This was also one of the findings of another recent study on parole conducted in Western Australia. In that study, Gately et al (2017) found that nearly two-thirds of the 38 interview respondents understood that parole involved releasing prisoners back into the community before completing their sentence, but many thought that this involved the sentence being shortened. In addition, although most respondents were aware of the concept of a 'parole board', there was limited understanding about how this worked.…”
Section: Australian Public Opinion On Parolementioning
confidence: 97%